2012
DOI: 10.1074/jbc.m111.297309
|View full text |Cite
|
Sign up to set email alerts
|

Novel Attributes of Hed1 Affect Dynamics and Activity of the Rad51 Presynaptic Filament during Meiotic Recombination

Abstract: Background: Hed1 attenuates the activity of Rad51 during meiotic recombination to allow Dmc1-dependent formation of interhomolog crossovers. Results: Hed1 possesses DNA binding and self-association activities and stabilizes Rad51 presynaptic filament. Conclusion: DNA binding, Rad51 interaction, and self-association are essential for Hed1 function as a key regulator of meiotic recombination. Significance: Our results shed light on the mechanism of interhomolog bias in meiotic recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 45 publications
4
46
2
Order By: Relevance
“…Therefore, as an alternative strategy, we used GFP-tagged Hed1 to detect to distribution of Rad51 with the mixed filaments. Genetic and biochemical data have demonstrated that Hed1 interacts specifically with Rad51 (15,39), and Hed1-GFP complements a hed1D strain, indicating that the fluorescent protein retains function (14). Consistent with these findings, we can readily detect Hed1-GFP binding to Rad51, but we are unable to detect any GFP-Hed1 association with Dmc1 ( Figure 2A) (40).…”
Section: Models For Mixed Recombinase Filaments -Rad51supporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, as an alternative strategy, we used GFP-tagged Hed1 to detect to distribution of Rad51 with the mixed filaments. Genetic and biochemical data have demonstrated that Hed1 interacts specifically with Rad51 (15,39), and Hed1-GFP complements a hed1D strain, indicating that the fluorescent protein retains function (14). Consistent with these findings, we can readily detect Hed1-GFP binding to Rad51, but we are unable to detect any GFP-Hed1 association with Dmc1 ( Figure 2A) (40).…”
Section: Models For Mixed Recombinase Filaments -Rad51supporting
confidence: 82%
“…Despite these many commonalities, Dmc1 is the recombinase responsible for performing strand invasion during meiosis (13). In contrast, Rad51 is actively downregulated by Hed1-and Mek1-mediated inhibition of its interactions with Rad54, which is a cofactor that is required for Rad51 strand invasion activity (11,(14)(15)(16)(17). However, Rad51 is required for normal progression through meiosis and promotes Dmc1 foci formation, consistent with a role for Rad51 as a Dmc1 accessory factor (6,7,13,18).…”
Section: Introductionmentioning
confidence: 99%
“…Hed1 would exert its role as part of the quiescence complex that keeps the sister-associated end from undergoing synthesis-mediated extension and ensuing IS-dHJ formation, in collaboration with Rad51 (Kim et al, 2010; Figure 1A). A role for Hed1 at a later stage in recombination has also been suggested by Tsubouchi and colleagues (Busygina et al, 2012). Hed1 may also act earlier, in concert with Dmc1 (above).…”
Section: Discussionsupporting
confidence: 60%
“…For mitotic recombination, Rad51 activity is promoted by so-called “mediator proteins” (Krejci et al, 2012) which include essential Rad51 loading factors (Rad55/57) and the PCSS complex (Psy1, Csm2, Shu1, and Shu2), which is important but not essential for Rad51 activity (Ball et al, 2009; Krejci et al, 2012; Shor et al, 2005; Tao et al, 2012; Qing et al, 2011; Sasanuma et al, 2013). In meiosis, Rad51 strand exchange is directly and specifically inhibited by meiosis-specific factor Hed1 (Busygina et al, 2012; Tsubouchi and Roeder, 2006). Rad51 modulator roles for partner choice are addressed below.…”
Section: Introductionmentioning
confidence: 99%
“…ER is often eliminated by recombinationdependent pairing process. In budding yeast, the strand exchange capacity of Rad51 is shut down to facilitate Dmc1-mediated interhomolog recombination (Tsubouchi and Roeder, 2006;Busygina et al, 2012). Moreover, a dmc1 mutation increased unequal sister chromatid recombination (Grushcow et al, 1999;Thompson and Stahl, 1999).…”
Section: Functional Divergence In Rad51-like Genes In Ricementioning
confidence: 99%